Influence of eNOS gene polymorphism on cardiometabolic parameters in response to physical training in postmenopausal women - Esposti, R. D. [UNESP]; Sponton, C. H. G. [UNESP]; Malagrino, P. A. [UNESP]; Carvalho, F. C. [UNESP]; Peres, E. [UNESP]; Puga, G. M. [UNESP]; Novais, I. P. [UNESP]; Albuquerque, D. M.; Rodovalho, C. [UNESP]; Bacci, M. [UNESP]; Zanesco, Angelina [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
The health-promoting effects of exercise training (ET) are related to nitric oxide (NO) production and/or its bioavailability. The objective of this study was to determine whether single nucleotide polymorphism of the endothelial NO synthase (eNOS) gene at positions -786T>C, G894T (Glu298Asp) and at the variable number of tandem repeat (VNTR) Intron 4b/a would interfere with the cardiometabolic responses of postmenopausal women submitted to physical training. Forty-nine postmenopausal women were trained in sessions of 30-40 min, 3 days a week for 8 weeks. Genotypes, oxidative stress status and cardiometabolic parameters were then evaluated in a double-blind design. Both systolic and diastolic blood pressure values were significantly reduced after ET, which was genotype-independent. However, women without eNOS gene polymorphism at position -786T>C (TT genotype) and Intron 4b/a (bb genotype) presented a better reduction of total cholesterol levels (-786T>C: before = 213 ± 12.1, after = 159.8 ± 14.4, Δ = -24.9% and Intron 4b/a: before = 211.8 ± 7.4, after = 180.12 ± 6.4 mg/dL, Δ = -15%), and LDL cholesterol (-786T>C: before = 146.1 ± 13.3, after = 82.8 ± 9.2, Δ = -43.3% and Intron 4b/a: before = 143.2 ± 8, after = 102.7 ± 5.8 mg/dL, Δ = -28.3%) in response to ET compared to those who carried the mutant allele. Superoxide dismutase activity was significantly increased in trained women whereas no changes were observed in malondialdehyde levels. Women without eNOS gene polymorphism at position -786T>C and Intron 4b/a showed a greater reduction of plasma cholesterol levels in response to ET. Furthermore, no genotype influence was observed on arterial blood pressure or oxidative stress status in this population.
Keywords: Exercise training; eNOS polymorphism; Oxidative stress; Nitric oxide; Women